Pelatihan Water Purifier Dengan Metode Aerasi dan Filtrasi Menggunakan Saringan Pasir Cepat Sebagai Solusi Penjernihan Air Sumur di Desa Citorek Timur - Ali Akbar; Amelia Indah Indriani; Rani Wulandari; Aziza Greyta Gifani; Nida Salsabila; Irnin Agustina Dwi Astuti (Jurnal Pengabdian kepada Masyarakat Radisi, 2021)
: East Citorek Village is one of the villages located in Cibeber Subdistrict, Lebak Regency, Banten Province. Based on observations in East Citorek Village there are problems faced by the community in an effort to maintain the environment and cleanliness. Well water in East Citorek Village is very smelly and yellow. It greatly affects public health. Based on these problems, we conduct community service activities in the form of socialization and training in making water purifiers with filtration and aeration method using a quick sand filter as well water purification that will be carried out in East Citorek Village. The method of community service is socialization and training. This activity is held in July-August 2021. The results of this training product are in the form of a water purifier that can be installed near the wells of east Citorek village. This activity received a positive response from the people of East Citorek village. With the water purifier tool can be used to clear well water and well water to be clean and healthy, so it is suitable for consumption.